STRATEGI INTERNALISASI NILAI BUDAYA LOKAL PADA ANAK MELALUI TARI EKA KARYA DI DESA NGRAWAN - Paranti, Lesa; Putri, Rimasari Pramesti; Hartono, Hartono; Widodo, Widodo (Jurnal Wawasan Pendidikan, 2026)
This study aims to analyze the strategy of internalizing the value of local culture in children through the Eka Karya Dance in Ngrawan Village, Getasan District, Semarang Regency. The study used a qualitative method with a sociology of dance education approach. Data were collected through observation, interviews, and documentation involving dance trainers, tourism village managers, and children involved in the practice and performance of the Eka Karya Dance. Data analysis used the interactive model of Miles, Huberman, and Saldana which includes data condensation, data presentation, and drawing conclusions. The results show that the internalization of the value of love for local culture occurs through three main strategies. First, participatory experiences in dance practice that enable children to learn about local culture through physical activity, movement exercises, and social interactions. Second, the representation of cultural values contained in the movements, themes, and accompanying lyrics of the Eka Karya Dance that represent the values of love for the village, harmony, mutual cooperation, and togetherness. Third, the experience of performing in various cultural activities such as the Ngrawan Art Festival, community entertainment events, and welcoming tourists that provide social recognition and foster a sense of pride in local culture. Research findings show that Eka Karya Dance not only functions as a medium for learning art, but also as a vehicle for forming cultural identity and strengthening children's love for local culture